Prevalence and associated risk factors of intestinal parasites among schoolchildren in Ecuador, with emphasis on the molecular diversity of Giardia duodenalis, Blastocystis sp. and Enterocytozoon bieneusi. - Estephany Tapia-Veloz; Mónica Gozalbo; Marisa Guillén; Alejandro Dashti; Begoña Bailo; Pamela C Köster; Mónica Santín; David Carmena; María Trelis (Public Library of Science (PLoS), 2023)
Background Intestinal helminths, including Soil-Transmitted Helminth (STH), and Gastrointestinal Protist (GP) infections are major contributors to the global burden of disease, particularly in low-income countries such Ecuador. Their epidemiology in these settings is largely unknown. Methodology This prospective cross-sectional study investigates the carriage of intestinal helminths, including STH, and GP in asymptomatic schoolchildren (3-11 years) in the Chimborazo and Guayas provinces, Ecuador. Single stool samples (n = 372) and epidemiological questionnaires on demographics and potential risk factors were collected from participating schoolchildren. Conventional microscopy examination was used as screening method, and molecular (PCR and Sanger sequencing) assays were used to further investigate the epidemiology of some GP. A multivariate logistic regression analysis was used to evaluate the strength of the association of suspected risk factors with the presence of helminths and GP. Principal findings At least one intestinal parasite species was observed by microscopy in 63.2% (235/372) of the participating schoolchildren. Enterobius vermicularis (16.7%, 62/372; 95% CI: 13.0-20.9) and Blastocystis sp. (39.2%, 146/372; 95% CI: 34.2-44.2) were the most prevalent among helminths and GP, respectively. Assemblages A (50.0%), B (37.5%) and A+B (12.5%) were detected within Giardia duodenalis and ST3 (28.6%), ST1 and ST2 (26.2% each), and ST4 (14.3%) within Blastocystis sp. Three genotypes, two known (A: 66.7%; KB-1: 16.7%) and a novel (HhEcEb1, 16.7%) were identified within Enterocytozoon bieneusi. Municipality of origin, household overcrowding, and poor sanitation and personal hygiene habits were risk factors for childhood intestinal parasites colonization. Conclusions/significance Despite massive government drug administration programs, STH and GP infection remain a public health concern in paediatric populations living in poor-resource settings. Molecular analytical methods are required to better understand the epidemiology of these intestinal parasites. This study provides novel information on the occurrence of Blastocystis sp. and E. bieneusi genetic variants circulating in Ecuadorian human populations.